An Analysis of Teachers’ Roles in Enhancing Students’ Discipline in Teaching and Learning Activities - Siti Nur Khasanah; Wakib Kurniawan (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to analyze the role of teachers in enhancing students’ discipline during the teaching and learning process.The research employs a qualitative approach with a descriptive method to illustrate how teachers perform their roles and implement strategies in shaping students’ disciplinary behavior. Data were collected through observation, interviews, and documentation, and subsequently analyzed using content analysis techniques. The findings indicate that students’ discipline is developed through several strategies, including guidance, habituation, teacher role modeling, and the application of educational sanctions. Teachers play a crucial role in fostering students’ self-awareness by explaining the importance of discipline, providing character education, and regulating student behavior. Nevertheless, some students were still found to be inconsistent in completing assignments and complying with classroom rules. The discussion reveals that students’ disciplinary motivation arises from both intrinsic awareness and extrinsic factors, particularly fear of punishment. Teacher strategies oriented toward dialogue, exemplary behavior, and support from the head of the madrasah contribute significantly to the creation of an orderly and conducive learning environment. In conclusion, the success of discipline formation largely depends on the synergy between teacher strategies, exemplary conduct, student participation, and support from the school principal. A consistent and dialogical approach has proven effective in establishing a more stable and productive culture of discipline in the classroom.